The Role of Reading Corners in Encouraging Reading Literacy in Grade V Students at Muhammadiyah Robbani Elementary School - Romadlona, Adinda Laila; Suhartono, Suhartono (Universitas Pendidikan Indonesia, 2025)
This research aims to describe the optimization strategies, describe constraints, and analyze the role of reading corners in encouraging reading literacy in grade V students of Muhammadiyah Robbani Elementary School. This study used a qualitative descriptive approach involving 20 Grade V Al Farabi students. Data were collected through interviews, observations, and documentation, then analyzed using reduction, display, and verification. Reading literacy was assessed through six indicators: frequency, duration, engagement in discussions, material variety, interest and motivation, and participation. Reading corner aspects were examined based on eight characteristics: design, book collection, location, literacy activities, teacher support, parental involvement, comfort, and accessibility. Findings revealed strategies to optimize reading corners, such as parental involvement in creating and donating books. Constraints included limited book collections and differences in students’ abilities and interests, making it difficult for teachers to facilitate discussions. Overall, reading corners play an essential role in promoting reading literacy by providing convenient classroom access and fostering engagement. The study presents several key implications: (1) reading corners represent a cost-effective and scalable approach to promoting reading literacy; (2) educators are encouraged to design reading corners that are both visually engaging and inclusive in terms of content and learning preferences; (3) future initiatives should focus on enriching book collections and incorporating interactive, literacy-based activities; (4) policymakers should provide sustained support to schools by ensuring access to adequate and culturally relevant reading materials; and (5) the development of early reading literacy skills should be prioritized as a foundation for long-term academic success.